Impact of food selection and usage pattern on consumers’ attitude towards food label information - Saxena, Meha; Sharma, M K; Jain , Ankita (Journal of Postharvest Technology, 2021)
As the world is shrinking, the markets are integrating and the customer base is expanding. Consumers have a variety of packaged foods to choose from. They have become conscious about what they eat and want to make an informed food choice. Though most of the consumers are aware of the importance of food labels, they are unable to comprehend entire information provided on the labels. This makes it very important to study the consumers’ attitude towards food label information. This paper focuses on measurement of consumers’ attitude towards food labels in terms usage pattern of food label information and food selection. A cross sectional exit survey was conducted for a sample of 230 respondents from 5 major cities of Rajasthan, India using ratio based stratified random sampling. ANOVA was used to measure variation in consumers’ attitude demographically and multiple regression was used to find the impact of usage pattern and food selection on consumers’ attitude. Most of the consumers have a positive attitude towards food label information and there is a significant variation in consumers’ attitude with respect to highest qualification and personal income. Usage pattern and food selection have a positive and significant impact on consumers’ attitude.